Evaluating alternatives to zinc oxide and antibiotics in nursery pig diets - Stevenson, Caitlyn M.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Producers aspire to reduce the use of antibiotics and ZnO in swine diets to limit antimicrobial resistance and negative environment impact. This 35-d study was conducted using 360 weanling pigs (DNA 200×400; 5.4±0.07 kg BW) to evaluate the effects of substituting medium chain fatty acids (MCFA) for carbadox and ZnO. Pens were allotted in a completely randomized design with 6 pigs/pen and 10 pens/treatment. The treatment diets: 1) control; 2) 3,000 ppm ZnO in Phase 1 and 1,500 ppm ZnO in Phase 2; 3) 50 g/ton carbadox; 4) 1% C6:C8:C10; 5) 1% Feed Energy R2 (Feed Energy Corp., Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Treatment diets were fed for 19 d, with a common diet fed from d 19 to 35 (Phase 3). In Phase 1 (d 0 to 7) ADG and ADFI had a significant difference (P<0.05) between ZnO, C6:C8:C10, and R2. Phase 2 (d 8 to 19) observed a significant difference (P<0.05) in ADG with ZnO and FORMI GML having greater ADG than other treatments. Phase 3 (d 20 to 35) had no significant difference in any response (P<0.05). Overall (d 0 to 35) pigs fed ZnO or carbadox had greater (P<0.05) ADG than those fed the control or R2 diets, pigs fed the C6:C8:C10 blend or FORMI had similar (P>0.05) ADG as those fed carbadox. During the common period, pigs fed ZnO continued to have greater (P<0.05) ADG than those fed R2, with other treatments being intermediate. There was no overall impact on G:F (P = 0.320). The results of this study suggest that although the MCFA did not improve weanling pig growth over ZnO and Carbadox, 1% FORMI GML may be a promising alternative. Thus, additional research regarding MCFA is warranted to effectively replace ZnO or antibiotics in pork production.
Keywords: Spring 2019